2017
DOI: 10.5588/pha.16.0099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 2014 Ebola outbreak on antenatal care and delivery outcomes in Liberia: a nationwide analysis

Abstract: All health facilities, public and private, in Liberia, West Africa. To determine access to antenatal care (ANC), deliveries and their outcomes before, during and after the 2014-2015 Ebola outbreak. This was a descriptive cross-sectional study. During the Ebola outbreak in Liberia, overall monthly reporting from health facilities plunged by 43%. Access to ANC declined by 50% and reported deliveries fell by one third during the outbreak. Reported deliveries by skilled attendants and Caesarian section declined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 13 publications
0
48
0
1
Order By: Relevance
“…These findings suggest the need for the development of best practices, coordinated responses, and larger global investments in public-sector health system strengthening efforts when responding to future global public health emergencies [ 34 ]. The emerging evidence from Sierra Leone [ 2 , 16 , 17 , 22 ], Guinea [ 3 , 4 , 11 , 15 ], and Liberia ([ 6 10 ] and our study) suggests that, in terms of morbidity and mortality, the collateral effects from the EVD outbreak on public-sector primary healthcare delivery will greatly exceed the direct effects from EVD infection. Analyses using population-based surveys in Liberia suggest that distrust of the government and the health system was the primary source of reduced health service demand during the EVD outbreak, rather than supply-side factors [ 29 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These findings suggest the need for the development of best practices, coordinated responses, and larger global investments in public-sector health system strengthening efforts when responding to future global public health emergencies [ 34 ]. The emerging evidence from Sierra Leone [ 2 , 16 , 17 , 22 ], Guinea [ 3 , 4 , 11 , 15 ], and Liberia ([ 6 10 ] and our study) suggests that, in terms of morbidity and mortality, the collateral effects from the EVD outbreak on public-sector primary healthcare delivery will greatly exceed the direct effects from EVD infection. Analyses using population-based surveys in Liberia suggest that distrust of the government and the health system was the primary source of reduced health service demand during the EVD outbreak, rather than supply-side factors [ 29 ].…”
Section: Discussionmentioning
confidence: 73%
“…Analyses using routine health information system (RHIS) data originating from Guinea and Sierra Leone have recently chronicled the effect of the EVD epidemic on the delivery of public-sector care for maternal, child, and reproductive health services, showing dramatic decreases during the Ebola outbreak (on the order of 50% declines) and sustained low levels not suggesting recovery [ 3 5 ]. Previous descriptive studies using RHIS data from Liberia have shown decreases in maternal and child health (MCH) indicators [ 6 , 7 ], malaria treatment [ 8 ], HIV testing [ 9 ], and tuberculosis diagnoses [ 10 ] during the EVD outbreak. Others have estimated that EVD-related disruptions in treating malaria alone will contribute to significantly more excess deaths than direct EVD-related mortality [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Public health crises, such as the 2014 outbreak of Ebola virus disease (EVD) in West Africa, risk disrupting MHS and progress made in maternal health outcomes, particularly in regions with weak existing health infrastructure. 3 There is evidence from the 2014 outbreak of EVD in Guinea, Liberia and Sierra Leone that shows a deterioration in uptake and provision of MHS, [4][5][6][7][8][9][10] while just two studies, both conducted in Sierra Leone, reported insignificant changes in access to MHS. 11 12 When compared with preoutbreak metrics,…”
Section: Introductionmentioning
confidence: 99%
“…6 Sixteen studies were conducted, and are assembled here for this special issue. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Through the study of routine data the performance of a wide range of programmes was assessed before, during and after the outbreak. These studies present data from mother and child health care services, the human immunodeficiency virus (HIV), tuberculosis, vaccination, malaria, malnutrition and non-communicable diseases programmes.…”
mentioning
confidence: 99%